Political Participation Of Beginners In The 2024 General Election In Cirebon City - Muhammad Fathur Alhajmi; Nia Kurnia Rizqiya Berampu; Iskandar Zulkarnaen; Moh Sutarjo (PT Publikasiku Academic Solution, 2024)
Political participation involves political awareness and faith in government, which is directly connected to the concepts of democracy and legitimacy. The relationship between political participation, democracy and legitimacy is very close. This research highlights the preparation of Cirebon City for the 2024 General Election with a focus on the participation of new voters. This research aims to explore the experiences and perspectives of new voters through interviews, documentation, and observation to understand their political participation in depth. In addition, this study also aims to record the efforts of the Cirebon City KPU in overcoming obstacles to the participation of new voters. This research uses a qualitative method with a phenomenological paradigm approach. Descriptive data, both written and oral, were collected directly from first-time voters through interviews, documentation, and observation. Descriptive research, as Whitney describes, plays an important role in building a systematic, accurate and factual narrative. The results of this study describe the phenomenon of political participation of novice voters in Cirebon City and reveal the relationship between various aspects that influence it. The research also notes the efforts of the Cirebon City KPU in overcoming obstacles to the participation of first-time voters, including the use of social media, especially TikTok, to effectively disseminate information and attract the attention of first-time voters. This research shows that the political participation of novice voters in Cirebon City has a close relationship with the concepts of democracy and legitimacy. The Cirebon City KPU's efforts in using social media as a means of communication have made a positive contribution in increasing the participation of novice voters ahead of the 2024 General Election. The narrative generated from this research not only describes the phenomenon of political participation, but also provides a deeper understanding of the various aspects that influence the participation of novice voters.